Assessing the factors influencing delivery method selection in pregnant women referred to Public hospitals in Shirazr - Vafaee, reza; Hosseini, fatemeh; Ghobadi Dashdebi, kamel; Momen bellah fard, mohamad jafar; Ghalandari, maryam; Gharlipour, zabihollah; Tavassoli, elaheh (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Although cesarean section is the preferred mode of delivery for some mothers ,the rate of cesarean section deliveries has increased to more than 50 percent in some countries. While the World Health Organization has emphasized, cesarean section be performed only based on the indication. This study will assesses the causes and factors influenced on choosing the delivery method in pregnant women referred to Public Hospitals in Shiraz. Material & Methods: A descriptive design was used to assess factors related to mothers’ decisions about mode of delivery. Using a cluster random sampling method, a total number of 417 Pregnant women admitted to hospitals in Shiraz were included in the study. Data were collected by a questionnaire and interview. Data were analyzed by Chi-square, and fisher exact test with using SPSS software. Findings: The results showed significant relation among factors Urbanity, Infant health status, Concern about genital injuries , Spouse views and Willingness to cesarean with choice of cesarean (p <0/05). Conclusion: Due to significant positive attitude of women’s towards the cesarean, rather than normal delivery, it is necessary to inform them about the advantages of normal delivery and health hazard which might cause by Cesarean to the mother and child. The change of women’s Knowledge and attitude about cesarean is needed to avoid further complication. Key Word: delivery, Cesarean, Public hospitals, Shiraz REFERENCES Alimohamaian M, S. M., Mahmoodi M, Ramezanzadeh F( 2003)[ The influence of maternal request on the elective cesarean section rate in maternity hospitals in Tehran, Iran]. Payesh Journal 2(2) 133-139(Persian). Cnattingius R , C. S., Notzon C (1998). Obstacles to reducing cesarean rates in a low cesarean seting:the effect of maternal age , height and weight. Obstetrics and Gynecology . 92(4 Pt 1) 501-506. Cunningham F, M. P., Leveno K( 1993) Cesarean section and cesarean hysterectomy . Williams’ Obstetrics. 19th ed texa Prentice Hail International, INC, 591-594. Cunningham FG (2001). Cesarean section and postpartum hysterectomy. in:cunningham FG; Norman FG.;larry CG, Williams’ Text book of Obstetrics: From Appleton & lange Asimond Schusler company, 537-64. Darvishi E, M. S., Nedjat S, Holakouie Naieni K( 2013)[ Experiences of women and gynecologists on the choice of delivery method: A qualitative research]. Health System Research Journal . 8(1) 59-68.(Persian) Decherncy , P. M. (1999) Current Obstetric and Gynecologic Diagnosis and Treatment. lange Medical Book 703-709. Fabri RH , Murta. E F.(2002)Socioeconomic factors and cesarean section rates. International Journal of GYnecology and Obstetrics . 76(1) 87-88. Faraji Darkhaneh R.Zahiri Sarvi Z, Farjad Bastani F( 2003)[Knowledge and attitudes of pregnant women towards birth methods]. Journal of Guilan University of Medical Sciences . 12(46) 69-75. Ghaffari M,, Akbarai Z , Khorshidi M, Hassanzadeh A( 2012)[ Health belief model-based education & reduction of cesarean among pregnant women: An interventional study]. Health System Research. Journal . 7(2) 200-208. Loverro G Greco P Vimercatia A et al( 2005). Maternal complications associated with cesarean section, Journal of Perinatal Medicine , 29(4) 322-326. Goulld JB,Davey BStafford R S. (1989). Socio-economic differences in rates of cesarean section. The New England Journal of Medicine . 321(4) 223-290. Lapman C Phelps A.( 1997) College students’ knowledge and attitudes about cesarean birth. Birth 24(3) 159-64. Naghibi KH, Montazeri K( 1991)[ Painless delivery or cesarean section. Which is better?] First ed. Isfahan: University of Medical Sciences Press (Persian). Negahban T, Ansari Jaberi A, Kazemi M ( 2006) Prefered method of delivery and it’s relevant causes in view of pregnant women referring to public and private clinics in Rafsanjan city. Journal of Rafsanjan University of Medical Sciences 5(3) 161-171(Persian). Poma P. (1998) Effect of departmental policies on cesarean delivery rates: A community hospital experience. Obstetrics and Gynecology 91(6) 1013-108. Rice PL Nakzook C (1998) Cesarean or vaginal birth: perception sand experience of Thai women in Australian hospital. Australian and New zeland Journal of Public Health 22(5) 604-680. Ryding EL( 1993) Investigation of 33 women who demanded a cesarean for personal reasons. Acta Obstetrica et Gynecologica Scandinavica . 72(4) 280-285. Schneider, F. G., Winn HN (2000) Cesarean section and vaginal birth after cesarean section. In: Clinical maternal: New York: Parthenon Press, 15-18. Schuitemaker N Van Roosmalen J Dekker G et al( 1997) Maternal mortality after cesarean section in the Netherlands. Acta Obstetrica et Gynecologica Scandinavica 76(4) 332-334. Tumbull D A Wilkinson C Yaser A et al (1999). Women’s role and satisfaction in decision to have a cesarean section. The Medical Journal of Australia . 170(12) 580-630. Wirakusmah FF 1995. Maternal and prenatal mortality/morbidity associated cesarean section in Indonesia. Journal of Obstetrics and Gynecology (Tokyo 1995) 21(5) 475-81. Assessing